Pengaruh Likuiditas, Profitabilitas, Solvabilitas dan Ukuran perusahaan terhadap audit delay tahun 2017-2019 - Rikki Atjuar Tumanggor; Mahmuddin Syah Lubis (Owner : Riset dan Jurnal Akuntansi, 2022)
IDX is the party that organizes and provides a system as well as a means to bring together offers to buy and sell shares, other parties with the aim of trading shares among them, investors. The timeliness of the company in publishing its financial statements to the general public and investors also depends on the timeliness of the auditors in completing their audit work. This timeliness is related to the benefits of the financial statements themselves. This research was conducted in a manufacturing company listed on the Indonesia Stock Exchange (IDX). This study aims to determine (1) profitability on audit delay, (2) solvency has an effect on audit delay, (3) liquidity has an effect on audit delay, and (4 ) firm size has an effect on audit delay. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX). The sample used in this study was selected by purposive sampling. Based on the predetermined sample criteria from 30 manufacturing companies listed on the Indonesia Stock Exchange (IDX), to test how the influence of the independent variable on the dependent variable is used multiple regression analysis techniques. The results showed that (1) liquidity had a negative effect on audit delay, (2) solvency had a negative effect on audit delay, (3) profitability had a negative effect on audit delay, and (4) firm size had a negative effect on audit delay. The research findings can be useful for authors, auditors and Indonesian public accounting firms (KAP) to be considered in conducting audits.